New species of the Neotropical spider genus Celaetycheus Simon, 1897 (Araneae: Ctenidae) - Polotow, Daniele; Brescovit, Antonio D. (Zootaxa, 2013)
Nine species of the Neotropical spider genus Celaetycheus Simon, 1897 are newly described. All the species are endemic to the State of Bahia, northeast of Brazil: Celaetycheus abara sp. nov., C. aberem sp. nov., C. acaraje sp. nov., C. beiju sp. nov., C. bobo sp. nov., C. caruru sp. nov., C. moqueca sp. nov., C. mungunza sp. nov. and C. vatapa sp. nov. A new generic diagnosis, species diagnoses and distributional maps are provided.